Clarifying the Meaning of Sustainable Business: Introducing a Typology From Business-as-Usual to True Business Sustainability. (June 2016) - Dyllick, Thomas; Muff, Katrin
While sustainability management is becoming more widespread among major companies, the impact of their activities does not reflect in studies monitoring the state of the planet. What results from this is a "big disconnect." With this article, we address two main questions: "How can business make an effective contribution to addressing the sustainability challenges we are facing?" and "When is business truly sustainable?" In a time when more and more corporations claim to manage sustainably, we need to distinguish between those companies that contribute effectively to sustainability and those that do not. We provide an answer by clarifying the meaning of business sustainability. We review established approaches and develop a typology of business sustainability with a focus on effective contributions for sustainable development. This typology ranges from Business Sustainability 1.0 (Refined Shareholder Value Management) to Business Sustainability 2.0 (Managing for the Triple Bottom Line) and to Business Sustainability 3.0 (True Sustainability).